Hydroxychloroquine as an adjunct therapy in the management of type 2 diabetes in pregnancy: study protocol for a randomised controlled trial - Basri, Nurul Iftida; A Wahab, Norasyikin; Mohammed Nawi, Azmawati; Ishak, Shareena; Murthi, Padma; Abd Rahman, Rahana (BMJ Publishing Group, 2026)
Introduction The increasing incidence of type 2 diabetes mellitus (T2DM) among women of reproductive age poses significant health risks for both mothers and their fetuses. Optimising blood glucose levels during pregnancy is particularly challenging, even with a combination of oral antidiabetic agents and insulin therapy. Hydroxychloroquine (HCQ) has been shown to lower glucose levels in non-pregnant populations and has demonstrated safety in pregnant women with systemic lupus erythematosus and rheumatoid diseases. In addition to its glucose-lowering effects, HCQ also exhibits immunomodulatory, antioxidant and anti-inflammatory properties. Given that both T2DM and pregnancy are pro-inflammatory states, inadequate glycaemic control may exacerbate adverse pregnancy outcomes. We hypothesise that adjunctive treatment with HCQ in this cohort could improve glycaemic control, reduce systemic inflammation and subsequently lower the risk of adverse pregnancy outcomes. Methods and analysis This is a prospective, open-label, randomised controlled trial involving 56 pregnant women diagnosed with T2DM. Participants will be randomly allocated, using computerised randomisation software, into either a control group receiving standard care or an intervention group receiving standard care with HCQ 200mg daily. The primary outcomes will be the difference in glycaemic parameters and inflammatory markers. Secondary outcomes include the assessment of pregnancy outcomes between the groups, such as gestational age at delivery, postpartum haemorrhage, fetal macrosomia and shoulder dystocia. Ethics and dissemination This protocol has been approved by the National University of Malaysia Ethics Committee (JEP-2023–866). Study findings will be disseminated via presentations at academic conferences, publications in peer-reviewed journals and professional training and meetings to healthcare professionals. Trial registration number This study was registered in ClinicalTrials.gov (NCT06319560) on 23 January 2024.